Rehearsing New Roles : How College Students Develop as Writers - Carroll, Lee Ann, 1946- (Book collections on Project MUSE., 2002)
In Rehearsing New Roles: How College Students Develop as Writers, Lee Ann Carroll argues for a developmental perspective to counter the fantasy held by many college faculty that students should, or could, be taught to write once so that ever after, they can write effectively on any topic, any place, any time. Carroll demonstrates in this volume why a one- or two-semester, first-year course in writing cannot meet all the needs of even more experienced writers. She then shows how students' complex literacy skills develop slowly, often idiosyncratically, over the course of their college years, as they choose or are coerced to take on new roles as writers. As evidence, Carroll offers a longitudinal study of a group of students and the literacy environment they experienced in a midsize, independent university. Her study follows the experiences that altered their conception of writing in college and fostered their growing capacities as writers. Carroll's analysis of the data collected supports a limited but still useful role for first-year composition, demonstrates how students do learn to write differently across the curriculum in ways that may or may not be recognized by faculty, and evaluates the teaching and learning practices that promote or constrain students' development. --